ANALISIS EKSPOR PT BINA MITRA MAKMUR - Aditia Ningtiyas; Chania Cyrda Claudia; Easter Victoria; Helena Milli (Journal of the Community Development in Asia (JCDA), 2018)
This study aims to analyze a product in a company in Indonesia, so that it can be exported to other countries and can add value to Indonesian products. PT Bina Mitra Makmur is a company originating from Jambi Indonesia. The PT produces palm oil. Providing several scales to products, markets, operations and company finances by groups. Is the company eligible to export. The type of payment made by PT Bina Mitra Makmur uses the type of payment of Letter of Credits (L / C), is an institution in the form of collateral issued by the bank at the request of the customer (aplicant) to pay a sum of money to the L / C recipient for submitting a set of documents according to the terms and conditions requested in the L / C. analyze palm oil crude products that can be exported to China, because China is the country with the most population and also the largest importer of oil. Human resources that will be needed in "Come on Export" activities. The human resources needed include workers in the company to produce palm oil, after that some human resources to unload containers to travel from the company to the port and from the port to the destination. Shipping that will be needed in export activities, the group has followed several procedures in shipping, especially at the Emirates Shipping Line. Analyze all finance (banks) that will be needed for export activities. Key Words : Ekspor, Palm Oil, type of payment, China, Human resources, Shipping, finance